Evaluation of the impact of monetary policy on the economic development of the Stavropol krai - A. E. Tomaily; V. A. Bredikhina; A. V. Krasnikov (Вестник Северо-Кавказского федерального университета)
Introduction. Regional monetary policy is a part of the national monetary mechanism and is carried out taking into account the characteristics of each region. Its goal is to ensure the socio-economic development of the regions through the use of monetary methods in combination with the unique characteristics of each region. Materials and methods. The study is based on the analysis of macroeconomic indicators of the region, as well as an assessment of the effectiveness of the monetary policy pursued by the Central Bank. Results and discussion. The study revealed that state bodies are engaged in the regulation of the financial and credit system and monetary flows of the region to ensure the stable development of the financial market and achieve high economic growth rates are the main problems faced by the regional economy. Conclusion. It can be concluded that the correct monetary policy can increase the level of economic development of the region, improve the investment climate and ensure the sustainable functioning of the economy.